2018
DOI: 10.1016/j.jlumin.2018.06.053
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the optical properties of luminescent down shifting layers based on organic dyes to increase the efficiency and lifetime of P3HT: PCBM photovoltaic devices

Abstract: Tuning the optical properties of luminescent down shifting layers based on organic dyes to increase the efficiency and lifetime of P3HT: PCBM photovoltaic devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…[125] Fernandes et al introduced the three different organic dyes and showed their absorption spectra below 450 nm and photoluminescence within the P3HT: PCBM active layer absorption range. [126] These are coumarim 7 (C7), coumarim 153 (C153), and kremer blue (KB). The metal/organic complex (Alq 3 ), and europium complex (Eu) were used to compared the dye's optical properties.…”
Section: Organic Molecules/dyesmentioning
confidence: 99%
“…[125] Fernandes et al introduced the three different organic dyes and showed their absorption spectra below 450 nm and photoluminescence within the P3HT: PCBM active layer absorption range. [126] These are coumarim 7 (C7), coumarim 153 (C153), and kremer blue (KB). The metal/organic complex (Alq 3 ), and europium complex (Eu) were used to compared the dye's optical properties.…”
Section: Organic Molecules/dyesmentioning
confidence: 99%
“…Since first reported by Hovel et al in 1979, LDS layers have been considered as one of the effective strategies to improve the efficiency of solar cells. So far, rare-earth doped phosphors, organic luminescent dyes, , and quantum dots (QDs) , have been reported as LDS materials. Among them, colloidal semiconductor QDs have attracted much attention due to their outstanding photoluminescence ,, and tunable emission wavelength by controlling their size. , Ternary I–III–VI semiconductor QDs, e.g., Ag- and Cu-based, play a pivotal role as an alternative to environmentally unfriendly Cd- and Pb-based QDs in optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…A luminescent downshifting (LDS) layer with phosphors is an active area of research toward improving the conversion efficiency of solar cells. Phosphors for the LDS layer include organic dyes, 4–8 rare-earth complexes, 2,9–11 and inorganic nanoparticles. 12–19 Organic dyes and rare-earth complexes are not suitable for use in solar devices; a durability of more than 20 years is required for solar modules.…”
Section: Introductionmentioning
confidence: 99%